Musculoskeletal melioidosis - Nuttaya Pattamapaspong (2018)
Melioidosis is an infectious disease caused by Burkholderia pseudomallei, mostly affecting patients in Southeast Asia and northern Australia. The disease has been increasingly recognized around the world due to the increased levels of travel and population movement. Clinical manifestations of melioidosis range from fulminant septicemic illness to an indolent local infection. The disease often involves multiple organs, including the lung, spleen, liver, and other visceral organs. Musculoskeletal infection is usually seen as a part of multiorgan involvement, but localized musculoskeletal involvement may occur. The most common manifestation of musculoskeletal melioidosis is septic arthritis, followed by osteomyelitis, pyomyositis, and soft tissue abscesses. The clinical and radiological manifestations of musculoskeletal melioidosis are nonspecific, and the diagnosis needs a high level of suspicion. Associated infection of lungs and visceral organs is suggestive of melioidosis. The disease requires special laboratory facilities and treatment. Inappropriate or inadequate treatment leads to high mortality rate or long-term relapse of the disease. The causative organism of melioidosis, clinical manifestations, and imaging features of musculoskeletal melioidosis are reviewed. © 2011 Thieme Medical Publishers, Inc.